Effect of primary tumor invasion on treatment and survival in extranodal nasal-type NK/T-cell lymphoma in the modern chemotherapy era: a multicenter study from the China Lymphoma Collaborative Group (CLCG). Issue 11 (19th September 2019) - Qi, Shu-Nan; Xu, Li-Ming; Yuan, Zhi-Yong; Wu, Tao; Zhu, Su-Yu; Shi, Mei; Su, Hang; Wang, Ying; He, Xia; Zhang, Li-Ling; Wu, Gang; Qu, Bao-Lin; et al.
Abstract: We evaluated the effect of primary tumor invasion (PTI) on treatment selection in 1356 patients with extranodal nasal-type NK/T cell lymphoma who received non-anthracycline-based chemotherapy from the updated dataset of China Lymphoma Collaborative Group. 760 (56.0%) patients had PTI. PTI showed most prominent effect in stage I disease, with 5-year overall survival (OS) of 83.0% in PTI-absent patients and 69.5% in PTI-present patients ( p < .001). Radiotherapy ± chemotherapy achieved higher OS in PTI-absent stage I patients (approximately 85%). Either radiotherapy alone or chemotherapy alone was associated with an unfavorable OS in PTI-present patients (approximately 55%). Compared to radiotherapy alone, combined modality treatment improved OS in PTI-present patients (78.3% vs. 56.6%; p = .001) but showed similar OS in PTI-absent patients (85.3% vs. 83.3%; p = .560). These findings were confirmed in multivariate analyses. PTI was a robust prognostic factor and indicator for additional chemotherapy in stage I NKTCL patients.